2008
DOI: 10.1152/ajpheart.01318.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sympathy for the devil: the role of thromboxane in the regulation of vascular tone and blood pressure

Abstract: Historically, the vasodilatory prostanoids, especially prostacyclin and prostaglandin E(2), are believed to contribute significantly to the regulation of normal vascular tone and blood pressure (BP), primarily by counteracting the prevailing effects of the systemic vasoconstrictor systems, including angiotensin II, the catecholamines, and vasopressin. In contrast, the primary vasoconstrictor prostanoid thromboxane A(2) (TxA(2)) is produced in far smaller quantities in the normal state. While TxA(2) is believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 84 publications
0
52
2
Order By: Relevance
“…TXA2 is produced primarily by platelets, but there is evidence of the synthesis of the vasoconstrictor metabolite by the endothelium (Sellers & Stallone 2008). E 2 did not change TXA2 production in our experiments.…”
Section: Discussioncontrasting
confidence: 56%
“…TXA2 is produced primarily by platelets, but there is evidence of the synthesis of the vasoconstrictor metabolite by the endothelium (Sellers & Stallone 2008). E 2 did not change TXA2 production in our experiments.…”
Section: Discussioncontrasting
confidence: 56%
“…Under this anesthetic condition, the rats were killed by exsanguination, and thoracic aortas were harvested. Thoracic aortic rings of 2.5 mm in length were studied in modified Krebs-Ringer's bicarbonate solution (control solution) of the following composition (in mM): NaCl 119, KCl 4.7, CaCl 2 2.5, MgSO 4 1.17, KH 2 PO 4 1.18, NaHCO 3 25, and glucose 5.5. Endothelial cells were removed mechanically by gentle rubbing of the lumen using a small forceps to avoid the modification mediated by endothelium-derived vasodilator substances as well as endothelial ATP-sensitive K ϩ channels.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Studies in cultured cells from pulmonary arterial endothelium and corpus cavernosum demonstrated that thromboxane A 2 , which is known as an eicosanoid derived from cyclooxygenase, increases superoxide production via the activation of NADPH oxidase. [3][4][5][6] However, it is still unclear whether thromboxane A 2 augments this enzymatic activity in the intact artery. Accumulating findings demonstrated that adenosine triphosphate (ATP)-sensitive K ϩ channels make significant contributions in the regulation of vascular smooth muscle tone under normal physiologic as well as pathophysiological conditions, 7 whereas increased oxidative stress reportedly induces malfunction of these channels.…”
mentioning
confidence: 99%
“…As platelets are anucleate, there can be no induction of COX-2 enzyme synthesis (Patrignani et al, 1999). Thromboxane A 2 can also be synthesized from endothelial cells (Sellers & Stallone, 2008). The third possibility is a transcellular formation of thromboxane A 2 by platelets from prostaglandin H 2 released by endothelial cells (Camacho & Vila, 2000).…”
Section: Prostanoids In Endotheliummentioning
confidence: 99%